ChemInform Abstract: A Mild and Efficient Synthesis of 3‐Hetarylamino‐s‐tetrazines. Issue 16 (28th March 2013) - Sheremetev, Aleksei B.; Palysaeva, Nadezhda V.; Struchkova, Marina I.; Suponitsky, Kyrill Yu.
Abstract Tetrazine (I) reacts with weakly based hetarylamines to afford compounds of 3, 5‐dimethylpyrazolyl group displacement [cf.